Pengoptimalan Jumlah Penyimpanan untuk Pengiriman Gas dengan Simulasi di PT X - Felita Felita; I Gede Agus Widyadana (Jurnal Titra, 2022)
This research was conducted to analyze the causes of the problems faced by PT X. The company is currently only able to make 46% of the 84 shipments in 2018. This is caused by the accumulation of isotank in the customer's area for a long time. Therefore, the company wants to invest in the addition of permanent storage in consumer areas, simulations are needed to find out the results obtained after the installation of storage. This research was conducted using Promodel simulation software to describe the current situation. The study was conducted in 2 stages, first modeling the initial conditions to obtain a basis for the proposed model, then simulating the proposal and analyzing whether the proposal that was carried out was influential or not. Results of simulation results show that with the addition of permanent storage, the total shipments owned by the company increased to 56% and got its investment capital back after 6.1 years and have present worth value Rp943.839.385.